Evidence for the involvement of Proline-rich Tyrosine Kinase 2 (PYK2) in tyrosine phosphorylation downstream of PKA activation during human sperm capacitation - Battistone, Maria Agustina (2014)
Sperm capacitation involves an increase in intracellular Ca(2+) concentration as well as in protein kinase A (PKA)-dependent protein tyrosine (Tyr) phosphorylation. Interestingly, in humans, a decrease in extracellular Ca(2+) concentration ([Ca(2+)]e) during capacitation induces an increase in Tyr phosphorylation indicating the complexity of Ca(2+) signaling during this process. In view of this, in the present study we further investigated the Ca(2+)-mediated signaling pathways implicated in Tyr phosphorylation during human sperm capacitation. Results revealed that sperm incubation in a medium without added Ca(2+) (e Ca(2+)) increased Tyr phosphorylation but did not modify PKA-mediated phosphorylation. Moreover, inhibition of either PKA or Src family kinase signaling cascades in e Ca(2+) down-regulated both PKA substrate and Tyr phosphorylations, indicating that the [Ca(2+)]e effects on Tyr phosphorylation depend on PKA targets. Inhibition of calmodulin or Ser/Thr protein phosphatase 2B also increased Tyr phosphorylation without affecting PKA-mediated phosphorylation, supporting the potential role of these Ca(2+) downstream effectors in the increase in Tyr phosphorylation observed in e Ca(2+). Experiments aimed to identify the kinase responsible for these observations revealed the presence of proline-rich tyrosine kinase 2 (PYK2), a focal adhesion kinase (FAK) family member, in human sperm, and the use of PF431396, an FAK inhibitor, supported the involvement of PYK2 in Tyr phosphorylation downstream of PKA activation. Results also showed that PYK2 was activated in e Ca(2+) as well as during capacitation and that PF431396 affected capacitated sperm motility, acrosome reaction and ability to penetrate both mouse cumulus matrix and zona-free hamster eggs. Together, our observations support PYK2 as an intermediary component of Ca(2+) signaling between PKA-mediated and Tyr phosphorylations that is required for achieving functional human sperm capacitation.